Implementation of a priori algorithm for book lending at state high school library I Silima Pungaga-Punga Parongil - Ningsih, Andini Yulistia; Volvo Sihombing; Sitorus, Sahat Parulian (Politeknik Ganesha Medan, 2021)
The library plays a role in helping students to enjoy reading books. The availability of books in various fields motivates students to come to visit the library, students / i can read or borrow library books. For this reason, the purpose of this research was carried out including helping library officials apply the rules of how to visit the libraries. In carrying out research methods, including conducting direct observations, conducting interviews to collect the necessary data. The pattern that will be analyzed is the pattern of borrowing what books are often borrowed so that library officials know the information of books that are often borrowed. The result obtained is with the application of a priori algorithms, book data is processed to produce a pattern of borrowing books. After all high frequency patterns are found, then the association rules are sought that meet the minimum requirement for associative confidence A→B minimum confidence = 25%. The final association rules are ordered based on minimum support and minimum confidence, if borrowing IPA, then borrowing MTK Support = 15%, Confidence = 42.8%.